Diversidade de fungos micorrízicos arbusculares em pomares e crescimento de mudas micropropagadas de mirtileiro - Farias, Daniela da Hora (2012)
Blueberries are temperate fruit species of great economic importance that has stood out in Southern Brazil. The objectives of this study were to evaluate the influence of arbuscular mycorrhizal fungi (AMF) on the production of plantlets of blueberry, as well as isolate and identify these fungi from the orchards in the South - RS. Samples were collected from soil and roots in experimental and commercial of blueberry orchards in the municipalities Pelotas, Morro Redondo and Jaguarão and ecological indexes used as a measure populations in orchards in the study and principal components analysis to assess the physical and chemical soil in relation to the AMF. We identified 18 different morphotypes of spores. The percentages of root colonization with AMF were high, ranging from 40 to 80%. Since the varieties in commercial orchard located in the city of Morro Redondo city were the most colonized in relation to others. The greatest number of spores found in O'Neal in the orchard from Micaela. The relative abundance and the highest Shannon diversity index (H ') and richness (R) were found in the older areas of cultivation, old orchard at Embrapa (EPV) and the commercial orchard in the Morro Redondo city (MR). The relative frequency shows the prevalence of species of the genus Glomus and Acaulospora in all orchards. The dominance evaluated by the Simpson index (Is) showed the same trend as the Shannon diversity and richness. Among the chemical parameters of soil, there was a high correlation of AMF species with varying pH, V (%), P and sand. AMF isolates for the production of seedlings were provided by Bank of species of the Department of Horticulture and Forestry at UFRGS. Were tested four species of AMF (Glomus clarum, Glomus etunicatum, Gigaspora margarita and Scutellospora heterogama) on the production of cultivars Woodard and Bluegem. The AMF would have positive effects in the nursery, particularly Gigaspora margarita which provided better nutrition, and higher biomass of plants growing Woodard and Glomus etunicatum Bluegem for cultivation. The efficiency of the mycorrhizal symbiosis of blueberry cultivars, depends on the interaction specifies AMF X host.